Newborn’s Mother With Preeclampsia: Risk For All Of The Life - Dávila-Aliaga, Carmen Rosa (2016)
Preeclampsia is a condition that affects pregnant women and is one of the leading causes of maternal death in Peru and the world, causing morbidity in both the mother and her newbom, in the most common problems in the neonatal age that associated with this pathology in neonates are: intrauterine growth restriction, small for gestational age, low birth weight, prematurity, metabolic disorders, clotting disorders, intraventricular hemorrhage, hyperbilirubinemia, respiratory distress, patent ductus arteriosus, necrotizing enterocolitis, hypotension, retinopathy , erosive gastritis, predisposition to infectious processes, including sepsis due to deficit in the activity of granulocyte chemotaxis and cytokines, etc. The impact of this disease continues throughout the life associating risk of diabetes mellitus, hyperlipidemia, hypertension, coronary artery disease, among others.